Are We Doing Enough to Reduce Ionizing Radiation Exposure in Children?: An Analysis of Current Approaches to Pediatric Appendicitis Imaging at a Major Urban Medical Center. Issue 4 (April 2020) - Iyer, Shweta; Patel, Juhee; Moscatelli, Marc; Narayanan, Nisha; Brunsting, Ella; Laub, Daniel; Hooley, Gwen; Tunik, Michael; Foltin, Jessica Cooper
Abstract : Objective: The aim of this study was to evaluate current imaging approaches in children with suspected appendicitis (AP) in the pediatric emergency department (ED) of a major urban medical center. Methods: Children aged 6 to 18 years who presented to a pediatric ED in 2016 with possible AP were identified by a keyword search. Charts were reviewed for the following: age, sex, time of evaluation, imaging study, results of imaging study, disposition, and outcome. Results: We calculated mean values and SD for continuous data. Initially, 503 charts were identified. Of these 503, 292 children were identified as having possible AP. Mean age was 10.7 years (SD, 2.7); 50.6% presented between 5:00 PM and 8:00 AM the next morning. Of the 287 US studies performed, 114 (39.7%) were definitively positive or negative. Of these, 46 (16.0%) were negative for AP and 68 (23.7%) were positive. There were 173 (60.3%) ultrasounds that were equivocal. Computed tomography scans were performed in 41 (13.9%) of the total 292 patients, and 2 (0.7%) of the 292 received magnetic resonance imaging. Patient dispositions were as follows: discharged home, 163 (55.8%); admitted for appendectomy, 69 (23.6%); admitted for observation, 37 (12.7%); and extended observation in ED, 10 (3.4%). There were 83 (28.4%) total surgical and interventional radiology cases and 209 (71.6%) nonsurgical cases. Of the 81 appendectomies, 79 (97.5%) had an abnormal appendix, and 2 (2.5%) had no AP. Of the 79 abnormal appendices, 22 (27.8%) were perforated, 55 (69.6%) were not, and 2 (2.6%) were unclear. Conclusions: Computed tomography scans were performed in 13.9% of patients with suspected AP. The overall AP rate was 28.4%. We plan to increase the use of magnetic resonance imaging and other modalities to reduce overall computed tomography usage.